Post-Pandemic Change Strategies in Indonesian Insurance: A Critical Literature Review Using a Systematic Interpretive Approach - Alvin Ayodhia Siregar (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines how Indonesia insurance industry adapted to the major disruptions caused by the COVID-19 pandemic, with particular attention to digital transformation, organizational change, leadership, workforce adaptation, and regulatory responses in the post-pandemic period.Methodology: This study uses a critical literature review approach, synthesizing 22 academic publications and professional reports published between 2020 and 2025. This review combines systematic search methods with interpretive analysis to identify key themes and evaluate the relevance and quality of each source.Results: The findings indicate that the pandemic accelerated digital adoption, redesigned service delivery, and intensified collaboration with insures firms. Many organizations lack structured change management frameworks, leading to inconsistent preparedness and uneven progress. The review also highlights that effective leadership, open communication, and workforce reskilling played a central role in successful adaptation while complying with regulatory adjustments that emphasized risk governance and encouraged digital and ESG-oriented reforms.Conclusion: The dynamics of change management in Indonesia insurance sector during and after the COVID-19 pandemic are examined. This study identifies three main domains of transformation such us digital acceleration and business model reconfiguration, leadership, culture, and workforce adaptation, and regulatory and risk governance transformation.Limitations: The study acknowledges limitations, largely due to the limited Indonesian-language research and industry developments that are not yet fully documented.Contribution: This study integrates crisis management, organizational ambidexterity, and adaptive change theories to explain the sector's post-pandemic transition and identifies key areas for future research on organizational learning and digital governance.